Jackie Chan's Indian play: immigration, Asianness, and the contracting self in the American settler colony. (1st October 2016) - Cornellier, Bruno
ABSTRACT: This paper is concerned with what I define as a cultural politics of 'being from' in the American settler colony. I use Tom Dey's Western/'cop-buddy' hybrid Shanghai Noon (2000), and most specifically what is presented in the film as actor Jackie Chan's failed and comedic partaking in the white and homosocial tradition of Indian play. I use the film as a textual anchor for the critical analysis of the types of contracting subjectivities that are implicitly privileged within the foundational delineations separating settlers, Natives, and arrivants in what President Obama described as a nation of immigrants that is carried on the back of the non-immigrant status of Native Americans. I explain that in his conversion from Chinese national to Asian American – a transition that is prefaced by his disqualification from the settler's exclusive struggle over nativeness, followed by his peculiar transition into an (Asian) American cowboy – Chan's character becomes representative of this dialectical (and, in his case, always already incomplete) movement from genealogy to autology, or from pre-modern forms of marriage, ethnic affiliations, and social constraints, to a settler-liberal ideal of intimacy, reasoned consent, and self-sovereignty. In other words, once Chan's character fulfils this trajectory of self-discovery in the refashioning of place and self, his new-found voice and sexuality bespeak his idiosyncratic conversion into an Asian American. I argue that his conversion illuminates some of the complex modalities of raced and gendered intimacy in settler articulations of the privileged, contracting subjectivity of liberal colonialism. What such representation of an idealized, autological migrant subject allows us to suggest, is that non-Native people of colour, as they re-enact themselves settler colonial modes of Native dispossession and/or co-optation, often remain peculiarly moored to the hegemonic structure of feeling of American settlerism in ways that often put upon them assimilationist demands that are parallel to those imposed upon Indigenous bodies as always incomplete white liberal subjects in the making.